2010
DOI: 10.1186/1476-4598-9-319
|View full text |Cite
|
Sign up to set email alerts
|

PC3 prostate tumor-initiating cells with molecular profile FAM65Bhigh/MFI2low/LEF1low increase tumor angiogenesis

Abstract: BackgroundCancer stem-like cells are proposed to sustain solid tumors by virtue of their capacity for self-renewal and differentiation to cells that comprise the bulk of the tumor, and have been identified for a variety of cancers based on characteristic clonal morphologies and patterns of marker gene expression.MethodsSingle cell cloning and spheroid culture studies were used to identify a population of cancer stem-like cells in the androgen-independent human prostate cancer cell line PC3.ResultsWe demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 64 publications
7
51
0
Order By: Relevance
“…T persicum extract induced an epithelial-like phenotype in PC-3 cells together with cell membrane localization of E-Cadherin and β-Catenin proteins ( Figure 5 and Figure 6). PC-3 prostate cancer cells have a mesenchymal phenotype and are very invasive and produce tumors in laboratory animals (Zhou et al, 2009;Kandouz et al, 2010;Zhang and Waxman, 2010;Tai et al, 2011). Our results showed that in these cells, both E-Cadherin and β-Catenin proteins were cytoplasmic and cells having either protein at the cell membrane were extremely rare (Figures 5 and 6).…”
Section: Discussionmentioning
confidence: 58%
“…T persicum extract induced an epithelial-like phenotype in PC-3 cells together with cell membrane localization of E-Cadherin and β-Catenin proteins ( Figure 5 and Figure 6). PC-3 prostate cancer cells have a mesenchymal phenotype and are very invasive and produce tumors in laboratory animals (Zhou et al, 2009;Kandouz et al, 2010;Zhang and Waxman, 2010;Tai et al, 2011). Our results showed that in these cells, both E-Cadherin and β-Catenin proteins were cytoplasmic and cells having either protein at the cell membrane were extremely rare (Figures 5 and 6).…”
Section: Discussionmentioning
confidence: 58%
“…2d,e). Previous studies demonstrated that the PC3 cell line retains a small fraction of cells (~1%) that can initiate serially transplantable tumors 32,33 and can be distinguished by their ability to form holoclones, which are small, dense colonies with a high capacity for self-renewal 34,35 . Remarkably, unlike control knockdown cells, PC3 cells stably depleted of BAZ2A were unable to form holoclones and meroclones (an intermediate phenotype of holoclones) and generated only paraclones, which retain no self-renewal capacity ( Fig.…”
mentioning
confidence: 99%
“…It has also been shown that holoclone-forming cells, cells whose progeny forms almost exclusively growing colonies, in prostate cancer specimens with the highest clonogenic potential were associated with stem cell phenotypes . More, the presence of large holoclones was also consistently observed in prostate cancer cell protaspheres (Li et al, 2008;Zhang & Waxman, 2010), suggesting that spheres with stem cell-like features have a higher proliferative potential. Indeed, protaspheres were capable of forming new generations of protaspheres and retained proliferative capacity as well as clonogenic potential after serial passages (Guzman-Ramirez et al, 2009).…”
Section: Protaspheresmentioning
confidence: 81%